Ballot box conservation: a study of local U.S. conservation measures and its use by local governments and planners - Clanahan, Christopher M. (Kansas State University, 2014)
As a legislative technique, the application of initiative or referendum is considered unconventional, yet frequently utilized to address local conservation issues throughout most of the United States. The subject of its appropriateness continues to remain under debate, especially in the field of planning. This longitudinal study employs a descriptive trend analysis on conservation measures conducted by local governments between 1996 and 2012, in order to identify any changes or consistencies in application. Subsequently, personal interviews were conducted with experienced local government officials to facilitate an understanding of current perceptions, specific experiences, and the outcomes relationship to comprehensive and capital improvement plans. Some key findings from this study include numerous relationships between ballot box conservation and election cycles, and a misperception by local governments of the passage capabilities of ballot box conservation. The inferences from this study will aid local governments and planners to consider or reconsider their stance on the use of ballot box conservation. Additionally, if local communities and governments do choose to practice or continue to practice the use of ballot box conservation, this study’s key findings will assist them in making their measures more successful.
Keywords: Ballot box conservation; Local government; Planning; Land conservation; Comprehensive plan; Voting; Political Science (0615); Social Research (0344); Urban Planning (0999)